Glia-Driven Brain Circuit Refinement Is Altered by Early-Life Adversity: Behavioral Outcomes - Milbocker, Katrina A.; Campbell, Taylor S.; Collins, Nicholas; Kim, SuHyeong; Smith, Eva A.; Roth, Tania L.; Klintsova, Anna Y. (Frontiers in Behavioral Neuroscience, 2021)
Early-life adversity (ELA), often clinically referred to as “adverse childhood experiences (ACE),” is the exposure to stress-inducing events in childhood that can result in poor health outcomes. ELA negatively affects neurodevelopment in children and adolescents resulting in several behavioral deficits and increasing the risk of developing a myriad of neuropsychiatric disorders later in life. The neurobiological mechanisms by which ELA alters neurodevelopment in childhood have been the focus of numerous reviews. However, a comprehensive review of the mechanisms affecting adolescent neurodevelopment (i.e., synaptic pruning and myelination) is lacking. Synaptic pruning and myelination are glia-driven processes that are imperative for brain circuit refinement during the transition from adolescence to adulthood. Failure to optimize brain circuitry between key brain structures involved in learning and memory, such as the hippocampus and prefrontal cortex, leads to the emergence of maladaptive behaviors including increased anxiety or reduced executive function. As such, we review preclinical and clinical literature to explore the immediate and lasting effects of ELA on brain circuit development and refinement. Finally, we describe a number of therapeutic interventions best-suited to support adolescent neurodevelopment in children with a history of ELA.